Perjuangan Hak Asasi Manusia dalam Novel Si Anak Badai Karya Tere Liye (Analisis Pembelajaran) - Santika, Cut; Fajrinur, Fajrinur (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2022)
This study aimed to describe the struggle for human rights and to describe the way in the Si Anak Badai novel by Tere Liye. This study used descriptive qualitative method. The data sources in this research were from Si Anak Badai novel by Tere Liye, which contained 318 pages. The research data were dialogues in Si Anak Badai novel which were classified into thirty human rights. The data were collected by using document review technique. After the data were collected, then, they were analyzed using descriptive method. The results showed that there were twenty eight human rights that were included in the research object. They were: being born free and receiving equal treatment, the right without discrimination, the right to life, the right without slavery, freedom from torture and degrading treatment, the right to recognition as a person before the law, the right to equality before the law, freedom protected by law, freedom from arbitrary arrest and exile, the right to a public hearing, the right to be presumed innocent until proven guilty, the right to privacy, the right to freedom of movement, the right to find a safe place to live, the right to marry and have a family, the right to own property, freedom of religion and thought, freedom of expression, the right to a general assembly, the right to democracy, the right to work and as a worker, the right to rest and leisure, the right to food and shelter, the right to education, the right to participate in the cultural life of society, the right to a just world, responsibility, freedom from other disturbances. The way in conveying the struggle for human rights was in the form of direct and indirect. In Si Anak Badai novel, lots of indirect form of delivery were found.